2020
DOI: 10.1039/c9tc05721h
|View full text |Cite
|
Sign up to set email alerts
|

Piezo-phototronic effect enhanced photodetectors based on MAPbI3 perovskite

Abstract: A novel piezo-phototronic effect enhanced photodetector based on MAPbI3 polycrystalline perovskite is designed and fabricated with reconfigurable piezoelectric performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 78 publications
0
23
0
Order By: Relevance
“…Furthermore, Nie et al demonstrated a piezophototronic effect enhanced PD array based on polycrystalline perovskite. [ 55 ] Compared with single‐crystal perovskite, polycrystalline perovskite materials are easier to prepare, lower environmental requirements, and higher conversion efficiency. Through systematic experiments, they studied the effects of excitation light, bias voltage, and different strain on the efficiency of polycrystalline perovskite PDs.…”
Section: Improvement In Pd Performance By Piezophototronic Effectmentioning
confidence: 99%
“…Furthermore, Nie et al demonstrated a piezophototronic effect enhanced PD array based on polycrystalline perovskite. [ 55 ] Compared with single‐crystal perovskite, polycrystalline perovskite materials are easier to prepare, lower environmental requirements, and higher conversion efficiency. Through systematic experiments, they studied the effects of excitation light, bias voltage, and different strain on the efficiency of polycrystalline perovskite PDs.…”
Section: Improvement In Pd Performance By Piezophototronic Effectmentioning
confidence: 99%
“…Ferroelectric EA 4 Pb 3 Br 10 SCFs as one kind of piezoelectric materials are expected to possess an effective piezoelectric coefficient, which may play a vital role in the piezoelectric device. [ 18–23 ] Figure 3c shows the lateral piezoresponse as a function of the driving voltage, which is correlated with the contact resonant frequency at the range of 240–260 kHz. [ 39,46 ] The amplitude values are verified by calibrating the resonant amplitude with the quality factor.…”
Section: Resultsmentioning
confidence: 99%
“…Note that EA 4 Pb 3 Br 10 SCF‐based photodetectors are endowed with spontaneous piezoelectric polarization that enables to modulate the separation and transportation of the photogenerated carriers induced by piezo‐phototronic effect. [ 20–23 ] Then, the PS membrane was stuck to a poly(ethylene terephthalate) (PET) substrate, and a manual stage was utilized in the strain engineering measurements. Figure S21, Supporting Information, displays the testing system under the conditions of applying tensile and compressive strains on the photodetectors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations